Penguatan Kapasitas Manajemen Sumber Daya Manusia untuk Peningkatan Kinerja Masyarakat di Lingkungan Kampung - Yosafat Fonataba; Esau Hombore; Ivone Agustina Nathan; Simon Yanuarius Konorop (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service aims to improve the capacity of human resources (HR) in Erambu Village, Merauke, through participatory-based training and empowerment programs to support the social and economic welfare of the community in a sustainable manner. The approach used involves identifying community needs through interviews, focus group discussions (FGDs), and direct observation. Intervention programs are designed based on the results of the identification, including job skills training, small business management, and effective HR management education. Program implementation is carried out through workshops, mentoring, and the formation of community-based business groups. Evaluations are carried out periodically using surveys and group discussions to measure the impact of the program on improving skills, income, and community participation in HR management. The results of the service show an increase in community awareness and capacity in managing HR independently, as well as a positive impact on economic welfare. Support from the village government and other stakeholders also contributes to the sustainability of the program. With a systematic monitoring and evaluation system, this program can be a model of empowerment that can be applied in other areas to create more competitive and competitive HR.